Detection of Altered Rock Zones by Applying the Essential Analyses of the Magnetic Method: A Case Study from the Lainea Geothermal Site, Southeast Sulawesi - La Hamimu; Al Rubaiyn; Suryawan Asfar; Laode Ihksan Juarzan; Indrawati Indrawati (Diponegoro University Semarang Indonesia, 2026)
The essential analyses in the magnetic method are fundamental approaches of geophysical studies that should be commonly applied for interpreting the magnetic data. In this study, the essential analyses of the magnetic method incorporated several fundamental techniques such as analytic signal processing, upward continuation technique, horizontal gradient method (HGM), tilt angle derivative (TDR), and Euler deconvolution. These techniques were successfully applied to process the field data acquired from the Lainea geothermal site, South Konawe District, Southeast Sulawesi Province, Indonesia. The results of the magnetic data processing were then analyzed to characterize the anomaly sources. This analysis is applied to the total magnetic intensity (TMI). Based on the application of all essential stages in processing and analysis of magnetic data, it was found that signal analysis and Euler deconvolution were effective and efficient in analyzing the magnetic anomaly source. Furthermore, from the TMI map it can be verified that a positive anomaly trend corresponding to the main fault and formation distribution. The HGM implementation can accurately detect the edge boundary of the body anomaly in the form of the altered rock. Here, there are several magnetic lineation paths trending in the north-south (N-S), northeast-southwest (NE-SW), and northwest-southeast (NW-SE) directions. The combined results of TDR and Euler deconvolution can completely show the detection of edge and depth of the anomaly. In particular, the altered rock zones can be specifically found at Boroboro fault, Windo fault, Kaindi fault, Laindi fault, and Lainea fault. A contact anomaly indicating rock intrusion was detected at a depth of 1300–1500 m, which may be associated with the development of altered rock zones.